ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA DALAM MENYELESAIKAN SOAL ARITMATIKA SOSIAL PADA SISWA KELAS VII SMP 15 AMALATU - Mila Karmila Sidik (THEOREMA: The Journal Education of Mathematics, 2023)
The purpose of this research is to describe the ability to solve mathematical problems solving social arithmetic problems in class VII students of SMP Negeri 15 Amalatu. The approach used in this study is a qualitative approach. The subjects in this study were class VII students of SMP Negeri 15 Amalatu. Then 3 students were taken from the research subjects representing the high, medium and low groups. The instruments in the research were problem-solving ability tests and interviews. As for the data analysis technique, namely, a) reduction, the things that are reduced are the answers from students who are out of sync with the interview questions in accordance with problem solving indicators. So that researchers will get a clearer picture and make it easier to carry out the next data collection, b) presentation of data, the purpose of presenting data is to find out the facts that occur in the field. In this study, the researcher uses a brief description to explain the data that has been obtained clearly and in detail, and c) in qualitative data analysis, namely drawing conclusions and verification. The first conclusion submitted is still tentative, will change if no evidence is found to help at the next stage of data collection. The results of the research Students who have high problem-solving abilities are: a) students can understand the problem, b) in solving S1 questions they do not write a solution plan, c) can solve the problem correctly even though they do not write a solution plan, d) can provide conclusions from each problem what was done. Students with moderate problem-solving abilities are: a) Masters did not write down the stages of understanding the problem but when interviewed Masters could understand the problem well, b) when solving questions Masters did not write down a solution plan, c) could solve the problem correctly even though he did not write down a solution plan, d) can provide conclusions from each problem that is done. Students with low problem-solving abilities are a) Doctoral students do not write down the stage of understanding the problem, b) in solving Master's questions they do not write down a solution plan, c) do not solve the problem correctly, d) cannot provide a conclusion from each problem that is done.